Patient With RHD Ec MR Severe, MS Moderate And Trombus In LV, When We Do The Surgeom In Cut Meutia Regional General Hospital - Yuri Savitri; Helma Humairah; Jauza Raudhatul Jannah Mendrofa; Nurul Afni; Della Vega Nisha Ayuna (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2022)
Rheumatic heart disease (RHD) is damage of the heart valves due to acute rheumatic fever (ARF) which results from the body’s autoimmune response to Streptococcus pyogenes (group A Streptococcus bacteria) infection which is a throat infection. Acute rheumatic fever is one of the most important causes of cardiovascular morbidity and mortality in the developing countries. A 25-years-old male patient, domiciled in Alue Dalam, Darul Aman, East Aceh, admitted to emergency department of Cut Mutia hospital, the patient was brought to the hospital by his family at 05.0o pm on January 27th, 2022. Patient referred from Graha Bunda hospital. Patient was admitted to the hospital with complaints shortness of breath. Shortness of breath is felt during activity and worsens at night. Shortness of breath since yesterday. The patient also complained of pounding. The pounding has been felt for five days before arriving at the hospital. The patient also has chest pain, and tired easily. Past medical history such hypertension and diabetes mellitus are denied. Physical examination before treatment was obtained: the patient looked restless, weakness, and akker. Echocardiography examination showed the MR Severe, MS moderate, AR moderate, TR moderate, PH mild, AML calsification, all chamber dilatation, and thrombus LV. The patient was given initial treatment in Cut Mutia General Hospital.